Transmission and Colonization of Pneumocystis jirovecii - Cristian Vera (MDPI AG, 2021)
Pneumocystis spp. was discovered in 1909 and was classified as a fungus in 1988. The species that infects humans is called P. jirovecii and important characteristics of its genome have recently been discovered. Important advances have been made to understand P. jirovecii, including aspects of its biology, evolution, lifecycle, and pathogenesis; it is now considered that the main route of transmission is airborne and that the infectious form is the asci (cyst), but it is unclear whether there is transmission by direct contact or droplet spread. On the other hand, P. jirovecii has been detected in respiratory secretions of hosts without causing disease, which has been termed asymptomatic carrier status or colonization (frequency in immunocompetent patients: 0–65%, pregnancy: 15.5%, children: 0–100%, HIV-positive patients: 20–69%, cystic fibrosis: 1–22%, and COPD: 16–55%). This article briefly describes the history of its discovery and the nomenclature of Pneumocystis spp., recently uncovered characteristics of its genome, and what research has been done on the transmission and colonization of P. jirovecii. Based on the literature, the authors of this review propose a hypothetical natural history of P. jirovecii infection in humans.